Adaptation of a model for integration of interventions for alcohol use disorders in primary health care in Tanzania - Dorothy Mushi; Charlotte Hanlon; Joel M. Francis; Moshiro Candida; Mekdes Demissie; Solomon Teferra (BMC Primary Care, 2023)
Abstract Background Integrating evidence-based interventions for people with alcohol use disorder (AUD) into primary healthcare (PHC) can increase access to care and reduce morbidity, mortality, and population burden. However, for the integration to be feasible, acceptable, and sustainable, there is a need to contextualize the approach and involve stakeholders. Therefore, this study aimed to use participatory methods to adapt a model for integrating AUD interventions in Tanzania’s PHC system at the community, facility, and organizational levels. Methods A mixed-methods study was used. Participants include key mental health stakeholders, experts, and PHC providers. We conducted a situational analysis to investigate opportunities and constraints in the existing systems of care, utilizing data available from the routine collection and/or in the public domain, individual semi-structured interviews (n = 11), and focus group discussions (3 groups; total n = 26 participants) and a series of theory of change (ToC) workshops (n = 32). Data from the three methods were triangulated to develop the adapted model for integrating interventions for AUD in PHC. Results A situational appraisal revealed limited community, facility, and organizational resources and infrastructures for supporting services delivery of integrated AUD interventions. Also, shortage of health workforce, inadequate health management information systems, and limited medical supply and financing. Nevertheless, the theory of change proposed integrated AUD intervention packages and strategies to facilitate integrated care for people with AUD. Additionally, the barriers and facilitators for implementing these integrated AUD interventions and how to overcome them were explored. Conclusions The adapted model for the integrated AUD intervention in Tanzanian PHC revealed limited resources and system functioning for facilitating integrated AUD services. Nevertheless, it proposes the needed integrated AUD interventions and its barriers, facilitators, and strategies for overcoming them. There is a need to pilot the adapted model to inform plans for more comprehensive implementation or scaling up.